Optimized preparation of urine samples from acute melioidosis patients for in-solution proteomic studies using LCMS QTOF or MALDI TOF MS - Pakeer, Aniza; Idorus, Mohd Yusri; Ismail, Nosrihah; Mariappan, Vanitha Mariappan; Mustafa Mahmoud, Mohammed Imad Al-Deen (IIUM Press, 2021)
Introduction: Investigation of urine proteome in patients with acute melioidosis may reveal potential disease markers, from either bacterial or human proteins. We used an in-solution gel-free method instead of 2-DE to detect human and Burkholderia pseudomallei proteins in urine of patients with acute melioidosis. Here, we propose a simpler, economical method for preparing urine samples directly from melioidosis patients, for in-solution proteomic analysis using LCMS-QTOF MS/MS or MALDI-TOF MS/MS. Material and Methods: We adapted an acetone-TCA based protein precipitation method with LCMS-QTOF MS to detect the B. pseudomallei proteins directly from urine of acute melioidosis patients (culture positive and negative). This process involves protein precipitation, desalting, trypsin digestion, and optimization for the mass spectrometry. Results: A total of 3,866 human peptides were detected across 11 urine samples from clinically suspected acute melioidosis patients. Among them were three Burkholderia specific proteins detected in 75% of culture positive samples. Large amounts of acute phase proteins, cell mediated immunity proteins, complement pathway proteins and inflammatory mediators were seen upon gene ontology (GO) annotation and GO enrichment analysis. Conclusions: This simple in-solution sample preparation method can be replicated easily for LCMS/MS-QTOF and MALDI-TOF proteomic analyses, avoiding tedious optimization steps in 2-DE. This method is cost effective and can be done in centres without specialized 2-DE or MS equipment and elutes can be easily transported for analysis and bioinformatics. This is the first study to analyse urine samples directly for B. pseudomallei proteins. Discovery of the entire proteome as a whole is important in leading to biomarker discovery.